The Analysis of Risk Level Effect on Credit Decision Making - nurul ilmi hairullah; Muhammad Sobarsyah; Andi Aswan (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2022)
The study aims to determine the risk level of credit decision making. The research is descriptive qualitative. The research is conducted in PT. Bank Rakyat Indonesia (Persero) Tbk. Makassar. Methods of collecting data uses library research method and field research method. The research data uses qualitative data obtained from the results of literature study. In addition to qualitative data, it is also used financial reports for three years. The results of this research indicated that to anticipate non-performing loans, the specifications of prospective debtors were carried out in each credit-granting process. In granting credit, the specifications for the prospective debtor must be carried out.